Peran Kurikulum Pembelajaran Dalam Memediasi Pemahaman Akuntansi Forensik Dalam Berprofesi Akuntan Forensik - Trifena Agustina; Siti Khairani (MDP Student Conference, 2026)
This study aims to examine the effect of forensic accounting understanding on students’ interest in pursuing a career as forensic accountants, with the perceived importance of the curriculum serving as a mediating variable. A quantitative correlational research design was employed in this study. Data were collected through questionnaires distributed to 126 accounting students from several universities in Palembang who had completed forensic accounting courses. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results indicate that forensic accounting understanding has a positive and significant effect on students’ interest in becoming forensic accountants. Furthermore, the learning curriculum significantly influences career interest. The mediation analysis reveals that the learning curriculum plays a significant mediating role in the relationship between forensic accounting understanding and career interest. These findings suggest that students’ understanding of forensic accounting is more effective in fostering career interest when supported by a relevant, structured, and practice-oriented curriculum. This study provides important implications for higher education institutions to strengthen the integration of forensic accounting into accounting curricula in order to develop competent and ethical graduates capable of addressing increasingly complex fraud issues.